2019
DOI: 10.3390/antibiotics8020065
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High Throughput Screen for the Identification of Inhibitors of Peptidoglycan O-Acetyltransferases, New Potential Antibacterial Targets

Abstract: The O-acetylation of peptidoglycan occurs in many Gram-negative and most Gram-positive pathogens and this modification to the essential wall polymer controls the lytic activity of the autolysins, particularly the lytic transglycosylases, and inhibits that of the lysozymes of innate immunity systems. As such, the peptidoglycan O-acetyltransferases PatA/B and OatA are recognized as virulence factors. In this study, we present the high throughput screening of small compound libraries to identify the first known i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…These strategies aim to weaken the bacterium’s pathogenicity without weakening the overall fitness of the bacterium, to the point that the antibiotic is seen as a large enough threat to warrant a resistance strategy. This is done by targeting virulence factors; for example, adhesion to inhibit host colonization, or O-acetylation (reviewed in [86,87]). The potential of PG O-acetylation as an attractive and viable anti-virulence target is underscored by results of a number of animal studies involving mutant strains of pathogens with reduced PG O-acetylation levels.…”
Section: Discussion: Targeting O-acetylation As a Novel Anti-virulmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies aim to weaken the bacterium’s pathogenicity without weakening the overall fitness of the bacterium, to the point that the antibiotic is seen as a large enough threat to warrant a resistance strategy. This is done by targeting virulence factors; for example, adhesion to inhibit host colonization, or O-acetylation (reviewed in [86,87]). The potential of PG O-acetylation as an attractive and viable anti-virulence target is underscored by results of a number of animal studies involving mutant strains of pathogens with reduced PG O-acetylation levels.…”
Section: Discussion: Targeting O-acetylation As a Novel Anti-virulmentioning
confidence: 99%
“…Targeting PG O-acetylation as an anti-virulence strategy represents a new avenue which is now being explored and has the potential to be a longer lasting solution. Recently, we demonstrated the possibility that inhibitors of PatB and OatA with antibacterial activity can be isolated [87] and thus provided a preliminary proof of principle that is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was conducted using CDD Vault Analysis Software (Collaborative Drug Discovery, Inc), and hits were identified as compounds that had a Z-score −3. The hits remaining after the primary and confirmatory screening were examined further to identify possible PAINS, which could result in false-positive results ( 91 ). Further refinement of the lead candidates was also conducted by assessing the fluorescence quenching potential of lead compound hits by assaying the quenching potential of different compound concentrations (10.1 μM and/or 50.5 μM) against the fluorescence of 4-methylumbeliferone (247 μM) to reveal any potential false positives that were not actually because of Ai WssI ΔN activity.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous in vitro molecular target-based HTS assays using the SML are reported to date that successfully identified inhibitors of various protein targets such as penicillin-binding protein (PBP) [ 178 ], mitogen-activated protein kinase (MKK) [ 179 ], the type III secretion system (T3SS) [ 180 ], the anthrax lethal factor (LF) [ 181 ], phosphopantetheinyl transferase (PPTase) [ 182 ], peptidoglycan O-acetyltransferase [ 183 ], telomere resolvase (ResT) [ 184 ], etc. Spicer et al screened ~292,000 compounds against M18 Aspartyl Aminopeptidase (PfM18AAP) and identified two compounds that were also active in whole cell-based assays [ 185 ].…”
Section: Synthetic Molecule Library (Sml) Screening For Antibacterial...mentioning
confidence: 99%